2013
DOI: 10.3389/fgene.2013.00061
|View full text |Cite
|
Sign up to set email alerts
|

The household contact study design for genetic epidemiological studies of infectious diseases

Abstract: Most genetic epidemiological study designs fall into one of two categories: family based and population-based (case–control). However, recent advances in statistical genetics call for study designs that combine these two approaches. We describe the household contact study design as we have applied it in our several years of study of the epidemiology of tuberculosis. Though we highlight its applicability for genetic epidemiological studies of infectious diseases, there are many facets of this design that are ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…The household contact study [16] started enrolling culture-confirmed TB patients and their households in Kampala, Uganda in April 2002, and this analysis includes patients enrolled through January 1, 2008 and followed through December 2010. An index case was defined as the first identified culture-confirmed TB case in the household.…”
Section: Methodsmentioning
confidence: 99%
“…The household contact study [16] started enrolling culture-confirmed TB patients and their households in Kampala, Uganda in April 2002, and this analysis includes patients enrolled through January 1, 2008 and followed through December 2010. An index case was defined as the first identified culture-confirmed TB case in the household.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have been family-based, while others used a traditional case-control design. The advantage of family-based studies of TB is that exposure is more certain even if variable [34, 35]. …”
Section: Previous Genetic Studies Of Tbmentioning
confidence: 99%
“…Stein et al (2013) describe a household contact study design which involves collecting data on households that may include both related and unrelated individuals. They argue that this research study design may be a powerful approach for jointly studying genetic and environmental exposures.…”
Section: Family Based Study Designsmentioning
confidence: 99%